Methamphetamine Injection Among Young Men Who Have Sex With Men: Risk for Human Immunodeficiency Virus Transmission in a Los Angeles Cohort - Gorbach, Pamina M (J Infect Dis, 2020)
BACKGROUND: Prevalence of methamphetamine (meth) injection and associated human immunodeficiency virus (HIV) risks among men who have sex with men (MSM) are unclear. METHODS: A total of 532 MSM completed 1880 mSTUDY study visits between August 2014 and June 2018 in Los Angeles, California. Assessments every 6 months included computer-assisted self-interviews and testing for sexually transmitted infections. Analyses by person and across visits adjusted for repeated measures. RESULTS: Of 532 participants, 51% (n = 276) reported meth use (past 6 months). Across 1880 visits, mutually exclusive substance use categories were as follows: 5% meth injection (5%), meth use without injection (33%), other substance use excluding meth (36%), and no substance use (26%). Comparisons across these categories respectively found that meth injectors reported higher prevalence of new sex partners (89%, 70%, 68%, and 51%, respectively), more were HIV positive (83%, 65%, 34%, and 50%), fewer were virally suppressed (53%, 48%, 61%, and 67%), and more had sexually transmitted infections (31%, 22%, 15%, and 15% (all P <.01). CONCLUSIONS: Among the young MSM reporting meth injection in this Los Angeles cohort, elevated risks of acquiring or transmitting HIV suggest that they contribute significantly to sustaining the local HIV epidemic. Preventing transition to injection use has potential for HIV prevention.